Enhancing University Students' Soft Skills: A Quantitative Study on Problem-Solving and Social Competence - Chen, Sizhuo; Lee, Say Wah (Journal of Ecohumanism, 2024)
This study investigates the development and interrelation of problem-solving skills and social competence among university students using the quantitative methodological approach. It addresses massive gaps in our knowledge regarding soft skill manifestation and evolution in higher education. Data was collected from 300 university students using validated survey instruments about problem-solving ability, social competence, academic performance, and other related variables through systematic sampling. There were a few significant positive correlations between problem-solving confidence, social competence, and academic performance. Multiple regression analysis demonstrated that problem-solving confidence and problem-solving skills are the principal predictors of academic outcome accounting for 25% of soft skill variance. Furthermore, the investigation indicates large substantive correlations between stress-coping mechanisms and social competence. This predicts that emotional resilience is influential in academic environments. This research analyzes the socioeconomic aspect of skill acquisition. Therefore, it underlines the need for specific education interventions. This contribution of the research to the theoretical discourse on the development of soft skills in higher education is further augmented by providing evidence-based recommendations for curriculum upgrading and institution policy reforms. The results of the study hold enormous implications for pedagogy practices and the development of education policy within higher education institutions.